Application of the Masquelet technique in austere environments: experience from a French forward surgical unit deployed in Chad - Choufani, Camille; Demoures, Thomas; de l’Escalopier, Nicolas; Chapon, Marie-Pauline; Barbier, Olivier; Mathieu, Laurent (European journal of trauma and emergency surgery (Munich : 2007), 2022)
Purpose We sought to evaluate the results of the Masquelet-induced membrane technique (IMT) for long bone defect reconstruction within the limited-resource setting of a French forward surgical unit deployed in Chad. Methods A prospective and observational study was conducted in all patients with a traumatic segmental bone defect in any anatomical location treated by IMT from November 2015 to December 2019. Although IMT was applied by various orthopedic surgeons with variable expertise, all followed the same surgical protocol. Endpoint assessment was performed 12 months after IMT application. Results Sixteen patients with a mean age of 32.7 years were included in the study. Bone defects were located on the tibia ( n = 8), the femur ( n = 6) or the radius ( n = 2). Thirteen bone defects were infected. After debridement, the mean bone defect length was 4.3 cm. External fixation of the tibia and femur was predominant in both stages. Bone union was achieved in only 8 of the 16 cases at a mean time of 7.6 months. All failures were related to persistent infection or insufficient fixation stability in the second stage. Conclusions This series is the first to report IMT use in a forward surgical unit. Despite frequent complications, local patients can benefit from this procedure, which is the only available method for bone reconstruction in areas with limited medical resources. A rigorous technical completion at both stages is crucial to limit septic or mechanical failures.